RET fusion mutation detected by re-biopsy 7 years after initial cytotoxic chemotherapy: A case report - Morikawa, Kei; Handa, Hiroshi; Ueno, Junko; Tsuruoka, Hajime; Inoue, Takeo; Shimada, Naoki; Koike, Junki; Nakamura, Seiji; Sato, Yoshiharu; Mineshita, Masamichi (Frontiers in Oncology, 2022)
Personalized medicine using molecular-targeted drugs to achieve better therapeutic response and long-term prognosis is common practice for lung cancer treatment. However, in cases before gene batch tests were available, medical treatment continued without the detection of rare mutations. We report a sixty-seven-old year man diagnosed with adenocarcinoma T1cN3M1a, stage IVA. Initial screening performed 7 years earlier using EGFR mutation and ALK immunohistochemical tests were negative. Although first-line cytotoxic combination chemotherapy was remarkably effective, a gradual regression of the primary lesion was noted. After a recent bronchoscopic re-biopsy, RET fusion was detected by gene panel test. In addition, we were able to confirm RET from FFPE specimens obtained from 7-year-old pleural effusion cell blocks. Subsequent administration of the molecular-targeted drug selpercatinib, was highly effective for the primary lesion and all metastatic lesions including brain metastases. We describe a case of RET fusion-positive lung cancer where molecular targeted therapy and cytotoxic drug showed a drastic response and long-term therapy was well maintained. Next generation sequencing was able to correctly diagnose RET fusion mutation using re-biopsy specimen after going undiagnosed for 7 years.